Doppler prediction of perinatal outcome in pregnancy induced hypertension and intrauterine growth retardation - Al-Azad, S; Rupa, SA; Khan, NA (Mymensingh Medical Journal, 2010)
Mymensingh Med J. 2010 Oct;19(4):510-4 The abstract of this article is available on the PubMed website